Association of the electrical parameters and photosynthetic characteristics of the tea tree manifests its response to simulated karst drought - Peng Wei; Haitao Li; Yanyou Wu; Cheng Zhang (Plant Signaling & Behavior)
Tea plantations in Karst regions suffer from the serious effects of frequent temporary karst droughts, leading to a decline in tea production and quality in the region. The close relationship between growth and electrical parameters of plants, including physiological capacitance, resistance and impedance, can be used to accurately monitor their plant water status online, quickly, accurately, timely and nondestructively. In this study, three tea tree cultivars of Zhonghuang No.2 (ZH), Wuniuzao (WNZ), and Longjing 43 (LJ) with different levels of drought resistance were selected as experimental materials, and experiments were carried out under controlled conditions according to control (soil water content of 40–45%, D0), (keeping D0 no watering to 5 days, D5), (keeping D0 no watering to 10 days, D10), (the first day after D10 is rehydrated to D0 is regarded as R1) and (the fifth day after D10 rehydration to D0 is regarded as R5), to determine intracellular water metabolism and nutrient translocation characteristics based on intrinsic electrical parameters. The photosynthetic characteristics and chlorophyll fluorescence parameters were also determined to investigate the response of water metabolism to simulated karst drought in the three tea tree cultivars. The results indicated that the water metabolism patterns responded to environmental water changes with a medium water-holding capacity, medium water transport rate, and low water-use efficiency, and the nutrient patterns in those tea tree varieties demonstrated with a high nutrient flux per unit area, low nutrient transfer rate, and high nutrient transport capacity. After rehydration, only the electrical characteristics of WNZ returned to the D0 levels, but the net photosynthetic rate of all varieties returned to or even exceeded the D0 levels. The chlorophyll fluorescence parameters could not be used to characterize the recoverability of metabolism in tea trees. The electrical characteristics quickly reflected the response of the water metabolism in plants to environmental changes, and the fusion of electrical characteristics and photosynthetic characteristics was able to more quickly, accurately, and comprehensively reflect the response of water metabolism to temporary karst drought.